Growth and Yield of Potato Solanum Tuberosum L. as Influenced by Soaking in GA3 and Potassium Fertilizer Rates - hamady, M. M. El- (Canadian Journal of Agriculture and Crops, 2017)
Gibberellic acid is a naturally occurring plant growth regulator which may cause a variety of effects, including the stimulation of seed germination by breaking seed dormancy. Gibberellins influence the dormancy of seeds, shoots, and other plant parts. Potato requires of balanced plant, mineral nutrients for growth and development without which yield and qualities of tubers are reduced. Potassium fertilizers are overlooked assuming that the soil is developed from K rich parent material and contains a sufficient amount of K to support crop growth. To achieve this aim, two field experiments were conducted during 2014 and 2015 seasons. Results revealed that increasing concentration of GA3 rates from 0 ppm GA3 to 30 ppm GA3 markedly increased plant height, chlorophyll content, foliage fresh and dry weight g/plant and No. of tubers/plant, tuber weight g/plant, tuber yield t/ha, TSS%, crude protein, tuber dry matter and starch %. It could be stated that increasing of GA3 rates from 0 ppm GA3 to 30 ppm GA3 significantly increased plant height, chlorophyll content, foliage fresh and dry weight g/plant and No. of tubers/plant, tuber weight g/plant, tuber yield t/ha, TSS%, crude protein, tuber dry matter and starch % by 8.82, 9.35, 4.5, 4.58, 34.7, 12.23, 12.48, 11.96, 25.15, 13.69 and 19.04 %, respectively as an average of both seasons. The results indicated that increasing potassium fertilizer rates from 0 kgK2O/ha to 172.5 kgK2O/ha markedly increased plant height, chlorophyll content, foliage fresh and dry weight g/plant and No. of tubers/plant, tuber weight g/plant, tuber yield t/ha, TSS%, crude protein, tuber dry matter and starch %. It could be noticed that increasing potassium fertilizer rates from 0 kgK2O/ha to 172.5 kgK2O/ha significantly increased plant height, chlorophyll content, foliage dry weight g/plant and No. of tubers/plant, tuber weight g/plant, tuber yield t/ha, TSS%, crude protein, tuber dry matter and starch % by 3.6, 10.83, 9.02, 16.18, 6.69, 6.62, 11.47,7.11, 7.1 and 4.66 %, respectively as an average of both seasons. It could be concluded that soaking seed tuber in 30 ppm GA3 and adding 172.5 kgK2O/ha maximized tuber yield and its quality.